Proceedings of the 10th ACM SIGCOMM Conference on Internet Measurement 2010
DOI: 10.1145/1879141.1879160
|View full text |Cite
|
Sign up to set email alerts
|

On the feasibility of effective opportunistic spectrum access

Abstract: Dynamic spectrum access networks are designed to allow today's bandwidth hungry "secondary devices" to share spectrum allocated to legacy devices, or "primary users." The success of this wireless communication model relies on the availability of unused spectrum, and the ability of secondary devices to utilize spectrum without disrupting transmissions of primary users. While recent measurement studies have shown that there is sufficient underutilized spectrum available, little is known about whether secondary d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 22 publications
0
19
0
Order By: Relevance
“…Each sweep over the entire 1.6GHz bandwidth takes about 1.8s and captures 8,192 samples, with each sample spanning 200kHz. Although the measurement data does not capture channel usage patterns shorter than 1.8s, channel statistics have been shown to remain unchanged at shorter time scales [15]. This strongly suggests that we can expect such statistics to be present at sufficiently small time scales to make RODIN useful.…”
Section: Simulation Setupmentioning
confidence: 96%
See 2 more Smart Citations
“…Each sweep over the entire 1.6GHz bandwidth takes about 1.8s and captures 8,192 samples, with each sample spanning 200kHz. Although the measurement data does not capture channel usage patterns shorter than 1.8s, channel statistics have been shown to remain unchanged at shorter time scales [15]. This strongly suggests that we can expect such statistics to be present at sufficiently small time scales to make RODIN useful.…”
Section: Simulation Setupmentioning
confidence: 96%
“…While this example deals with WiFi networks for clarity in exposition, the infeasibility of enhancing throughput by merely increasing bandwidth is also prevalent in non-WiFi networks. For example, a study of GSM usage patterns [15] shows that a wideband device cannot operate within the GSM band without some form of spectrum agility.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Authors in [18] have monitored a wide spectrum range (20MHz-6GHz) from three countries and reported that 54% of spectrum is never used and 26% is partially in use. Other work [10,21] has found substantial spectrum resources in TV whitespaces, and proposed different spectrum database designs to better predict vacant TV spectrum.…”
Section: Related Workmentioning
confidence: 99%
“…Although the existing dynamic spectrum access schemes have greatly improved the spectrum utilization efficiency, due to the mobility of nodes and the dynamics of the channel variation, the accuracy of players' decisions is limited and remains a challenge to fully utilize the scarce spectrum resources [12]. Nevertheless, players in a cognitive network are generally intelligent and able to optimize their performance.…”
Section: Introductionmentioning
confidence: 99%